Antineuroinflammatory and neurotrophic effects of CNTF and C16 peptide in an acute experimental autoimmune encephalomyelitis rat model - Fang, Marong; He, DaQiang; Zhang, Fan; Hu, Zhiying; Yang, Jing; Jiang, Hong; Han, Shu (Frontiers in Neuroanatomy, 2013)
Experimentalallergic encephalomyelitis (EAE) is an animal model for inflammatory demyelinating autoimmune disease, i.e., multiple sclerosis (MS). In the present study, we investigated the antineuroinflammatory/neuroprotective effects of C16, an ανβ3 integrin-binding peptide, and recombinant rat ciliary neurotrophic factor (CNTF), a cytokine that was originally identified as a survival factor for neurons, in an acute rodent EAE model. In this model, C16 peptide was injected intravenously every day for 2 weeks, and CNTF was delivered into the cerebral ventricles with Alzet miniosmotic pumps. Disease severity was assessed weekly using a scale ranging from 0 to 5. Multiple histological and molecular biological assays were employed to assess inflammation, axonal loss, neuronal apoptosis, white matter demyelination, and gliosis in the brain and spinal cord of different groups. Our results showed that the EAE induced rats revealed a significant increase in inflammatory cells infiltration, while C16 treatment could inhibit the infiltration of leukocytes and macrophages down to 2/3-1/3 of vehicle treated EAE control (P<0.05). The delayed onset of disease, reduced clinical score (P<0.01) in peak stage and more rapid recovery also were achieved in C16 treated group. Besides impairing inflammation, CNTF treatment also exerted direct neuroprotective effects, decreasing demyelination and axon loss score (P<0.05 Vs vehicle treated EAE control), and reducing the neuronal death from 40%-50% to 10%-20% (P<0.05). Both treatments suppressed the expression of cytokine tumor necrosis factor-α and interferon-when compared with the vehicle control (P<0.05). Combined treatment with C16 and CNTF produced more obvious functional recovery and neuroprotective effects than individually treatment (P<0.05). These results suggested that combination treatment with C16 and CNTF, which target different neuroprotection pathways, may be an effective therapeutic alternative to traditional therapy.